A global dataset of fossil fungi records from the Cenozoic - Emily Hodgson; Jessica McCoy; Kerry Webber; Noelia Nuñez Otaño; Jennifer O’Keefe; Matthew Pound (Scientific Data)
Abstract There is a substantial geologic record of microfossils belonging to the fungal kingdom, however there is a need for a curation of these fossil fungi records which is up-to-date, convenient, and manipulable. Here we present MyCeno (Mycology of the Cenozoic) 2.0: a dataset containing more than 3,000 records of fossil fungi from the Cenozoic era (66 million years ago to present) and from more than 200 locations around the world. These records represent a variety of fungal body parts, but most frequently fungal spores and spore-bearing structures. Detailed information about the locations, age estimations, geology, nomenclature, and taxonomy has been collected for every record. This dataset is an access point for people wanting to utilise fossil fungal records from the Cenozoic. It can be used for understanding fungal evolution, reconstructing past environments, and studying the impacts of climate change on biodiversity during the Cenozoic.